2015
DOI: 10.1111/jpn.12418
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value of electron beam irradiated cottonseed meal in broiler chickens

Abstract: This study was conducted to evaluate the effect of electron beam-irradiated cottonseed meal on performance, carcass characteristics and some blood parameters of broiler chicks. Treatments were cottonseed meal (CSM) at levels of 12% and 24% (raw and irradiated at 30 kGy) and corn-soya bean meal diet (as control, without CSM and without irradiation) that used with five dietary treatments, four replicates and 10 birds of each for 42 days in completely randomized design. Feed intake (FI) and body weight gain (BWG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Adding indigestible materials, such as wood shavings, can tremendously increase the weight of gizzard [27]. Other studies have linked the fibre content in dietary ingredients, such as CSM with hypertrophy of the GIT, including the gizzard [28,29]. Although, the fibre content of the formulated diets in this feeding trial was similar to the standard recommended by Aviagen [13], but CSM fibre tends to be physically bulky [30].…”
Section: Visceral Organ Weightsmentioning
confidence: 64%
See 1 more Smart Citation
“…Adding indigestible materials, such as wood shavings, can tremendously increase the weight of gizzard [27]. Other studies have linked the fibre content in dietary ingredients, such as CSM with hypertrophy of the GIT, including the gizzard [28,29]. Although, the fibre content of the formulated diets in this feeding trial was similar to the standard recommended by Aviagen [13], but CSM fibre tends to be physically bulky [30].…”
Section: Visceral Organ Weightsmentioning
confidence: 64%
“…The earlier work of Brenes et al [31] also found that the weights of visceral organs (liver, pancreas, small intestine and proventriculus) were not affected by wheat or xylanase. Nayefi et al [29] observed an increased weight of the gizzard and the rest of the GIT in birds fed CSM-containing diets.…”
Section: Visceral Organ Weightsmentioning
confidence: 98%
“…[38] reported that antinutritional factors like phytic acid, non-starch polysaccharides, and trypsin-inhibitor in rice bran attenuate broiler chicks growth performance. Phytate is an ionic reactant that can depress mineral availability through minerals integrating and hence degrades their solubility and reduce the digestibility of amino acid [39]. This effect indicated that -irradiation is efficient to hydrolyze the anti-nutritional bonds and indigestible compounds to a more simple form within MLM which seems to lead to better digestion in the rabbit's gastrointestinal tract.…”
Section: Impact Of Experimental Treatments On Rabbit's Performance 1-live Body Weight and Gain Weight (G)mentioning
confidence: 99%